BS EN IEC 61300-3-33. Fibre optic interconnecting devices and passive components. Basic test and measurement procedures. Part 3-33. Examinations and measurements. Withdrawal force from a resilient alignment sleeve using pin gauges (16th October 2020) - British Standards Institution,
No abstract available